Marriage and Persons with Disabilities – Current Trends and Reflections - Anju Adhikari (RIRAI Publisher, 2020)
Indian society attaches a lot of importance to marriage. Marriage is regarded as one of the most significant life cycle rituals. In traditional Hindu society marriage is considered a sacrament and therefore expected to be for life. It is the most formally recognized institution under which the progeny is accepted. In India marriage is an important institution since it is advised by “dharma” and also gives you a sense of attachment and belonging towards each other. However, marriage seems to be an unattainable goal to many persons with disabilities. The persons with all kinds of physical disabilities have a hard time finding partner for the marriage because many people in the society cannot look beyond the appearance of a disability. Persons with disabilities have abridged marriage prospects, less choice of a partner, higher dowries and greater risk of desertion. There is a paucity of research studies, especially in Indian context to understand the need for marriage and marital concerns of persons with physical disabilities. This empirical research highlights the need and importance of marriage for the persons with physical disabilities. It also suggests the suitable social work intervention model for marriage needs of persons with physical disabilities keeping their specific needs and requirements in mind.